2015
DOI: 10.3748/wjg.v21.i1.60
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hepatitis, one disease with many faces: Etiopathogenetic, clinico-laboratory and histological characteristics

Abstract: Autoimmune hepatitis (AIH) is an unresolving progressive liver disease of unknown etiology characterized by hypergammaglobulinemia, autoantibodies detection and interface hepatitis. Due to the absence of specific diagnostic markers and the large heterogeneity of its clinical, laboratory and histological features, AIH diagnosis may be potentially difficult. Therefore, in this in-depth review we summarize the substantial progress on etiopathogenesis, clinical, serological and histological phenotypes of AIH. AIH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
184
0
29

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(216 citation statements)
references
References 254 publications
3
184
0
29
Order By: Relevance
“…Using the original histologic criteria, simplified score of 46 was observed in 69% of autoimmune hepatitis cases, which is lower than observed in the original study but within the 65-95% range reported in literature. 3,4,6 When the total simplified score was calculated on the basis of the modified histologic criteria, there was an increase of autoimmune hepatitis cases with score 46 to 86%. In other words, 17% of autoimmune hepatitis cases that would have been labeled as non-autoimmune hepatitis based on the simplified criteria using the current histologic features would have been classified as probable or definite autoimmune hepatitis by the use of modified histologic features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the original histologic criteria, simplified score of 46 was observed in 69% of autoimmune hepatitis cases, which is lower than observed in the original study but within the 65-95% range reported in literature. 3,4,6 When the total simplified score was calculated on the basis of the modified histologic criteria, there was an increase of autoimmune hepatitis cases with score 46 to 86%. In other words, 17% of autoimmune hepatitis cases that would have been labeled as non-autoimmune hepatitis based on the simplified criteria using the current histologic features would have been classified as probable or definite autoimmune hepatitis by the use of modified histologic features.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 Multiple studies have established the key role of liver biopsy in autoimmune hepatitis, 3,10,16 and the practice guidelines of American Association for the Study of Liver Diseases as well as European Association for Study of Liver advocate the use of liver biopsy for diagnosis and treatment decisions. 25,26 The simplified criteria proposed by International Autoimmune Hepatitis Group mandate the presence of three histologic features in the same biopsy for the Autoimmune hepatitis: histologic criteria proposal case to qualify as a histologically 'typical' (2 points): interface lymphocytic/lymphoplasmacytic inflammatory activity, rosettes, and emperipolesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pesar de no conocerse la causa específica de la enfermedad, se considera que se desarrolla en personas con predisposición genética que se exponen a algún agente desencadenante como bacterias, virus, hongos u otras partículas externas al organismo 9,10 ; la caracterización del cuadro clínico es de amplio rango presentándose desde formas asintomáticas solo detectables por elevaciones moderadas de las aminotransferasas hasta casos de hepatitis severa fulminante 1, 11,12 . De esta forma, la mayoría de los pacientes son asintomáticos o presentan formas leves de la enfermedad, siendo los síntomas generales inespecíficos como astenia, fatiga y debilidad un motivo de consulta frecuente.…”
Section: Introductionunclassified
“…The mechanisms underlying the onset of autoimmune hepatitis remain unclear. However, the main hypothesis postulates that disease susceptibility is affected by both genetic and environmental factors that lead to a loss of tolerance towards liver antigens (2).…”
Section: Introductionmentioning
confidence: 99%